Análise da metodologia para definição dos limites de continuidade dos conjuntos elétricos das distribuidoras de energia elétrica no Brasil - OLIVEIRA, Loreddana Monteiro Bandeira de (Universidade Federal do Pará, 2025)
The definition of continuity indicator limits for electrical network sectors in electricity distribution companies represents the primary regulatory aspect of electricity supply quality, directly impacting consumer tariffs and investment decisions made by electric companies in electricity distribution systems. In the context of electricity sector regulation, maintaining continuity indices at appropriate levels is crucial to improving supply for consumers and ensuring tariff accessibility. This study presents the Brazilian regulation of collective continuity indicators for electricity supply, developed by the National Electric Energy Agency (ANEEL), from its implementation to the present, analyzing how each regulatory change has influenced the performance and development of the Brazilian electricity sector, with particular emphasis on the State of Pará. Pará exhibits unique continuity indicators compared to other states due to its concession area characteristics, including access challenges, long distances, and low population density. ANEEL uses benchmarking among distribution companies’ electrical sectors to establish performance targets at the end of each tariff cycle; however, the current method for setting regulatory limits does not account for factors that directly impact operational management or specific regional characteristics. This dissertation aims to analyze the current methodology for defining continuity limits for the electrical network sectors of electric companies in Brazil.